Getting ahead of Alzheimer’s disease: early intervention with focused ultrasound - Noel, Rebecca L.; Gorman, Samantha L.; Batts, Alec J.; Konofagou, Elisa E. (Frontiers in Neuroscience, 2023)
The amyloid-β (Aβ) hypothesis implicates Aβ protein accumulation in Alzheimer’s disease (AD) onset and progression. However, therapies targeting Aβ have proven insufficient in achieving disease reversal, prompting a shift to focus on early intervention and alternative therapeutic targets. Focused Ultrasound (FUS) paired with systemically-introduced microbubbles (μB) is a noninvasive technique for targeted and transient blood-brain barrier opening (BBBO), which has demonstrated Aβ and tau reduction, as well as memory improvement in models of late-stage AD. However, similar to drug treatments for AD, efficient treatment is not sufficient for advanced, symptomatic AD. Here we aimed to determine whether early intervention with FUS-BBBO in asymptomatic AD could delay disease onset. Thus, our objective was to measure the protective effects of FUS-BBBO on anxiety, memory and AD-associated protein levels in female and male triple transgenic (3xTg) AD mice treated at an early age and disease state. Here we show that early, repeated intervention with FUS-BBBO decreased anxiety-associated behaviors in the Open Field test by 463.02% and 37.42% in male and female cohorts respectively. FUS-BBBO preserved female aptitude for learning in the Active Place Avoidance paradigm, reducing the shock quadrant time by 30.03% and 31.01% in the final long-term and reversal learning trials respectively. Finally, FUS-BBBO reduced hippocampal accumulation of Aβ40, Aβ42 and total tau in females by 12.54%, 13.05% and 3.57% respectively, and reduced total tau in males by 18.98%. This demonstration of both cognitive and pathological protection could offer a solution for carriers of AD-associated mutation carriers as a safe, noninvasive technique to delay the onset of cognitive and pathological effects of Alzheimer’s disease.